Pengaruh Net Profit Margin, Earning Per Share, Inflasi dan Nilai Tukar Rupiah Terhadap Harga Saham - Agnes Santika; Yulianita Rahayu; Nani Ernawati; Juju Zuhriatusobah HS (Politeknik Ganesha Medan, 2023)
The stock exchange determines the share price for the activities carried out by the seller and buyer of shares. Supply and demand influence stock prices, so they can change at any time. Changes in stock prices can be seen from the company's internal and external factors. Internal factors occur within the company, such as company performance, and can be controlled by company management. While external factors are factors that appear outside the company's control but can have an impact on company performance. This study aims to determine the effect of Net Profit Margin, Earning Per Share, Inflation, and Rupiah Exchange Rate on stock prices simultaneously and partially. The research method uses a quantitative approach. The population in this study is the Tobacco and Non-durable Household Product, as many as 15 companies. Sampling was done by purposive sampling technique, so the sample number in this study was six companies. Data processing uses a tool, namely the E-views 12 Student Version. The F test results show that the Net Profit Margin, Earning Per Share, Inflation, and the Rupiah Exchange Rate simultaneously have a significant effect on stock prices. The results of the t-test show that the Net Profit Margin and Earning Per Share impact stock prices. Meanwhile, Inflation and the Rupiah Exchange Rate have no impact on the Stock Price. This research found that internal factors proxied through Net Profit Margin and Earning Per Share affect the Tobacco and Non-durable Household Product for the period 2012-2021. Meanwhile, external factors that are proxied through inflation and the Rupiah exchange rate do not affect stock prices.